Conceptualization of alternative food networks in Latin America: a case study of a local food system in Southwestern Colombia - Maysels, Rachael; Figueroa Casas, Apolinar; Otero Sarmiento, Juan Diego; Zuñiga Meneses, Shiomara Mileydi (Frontiers in Sustainable Food Systems, 2023)
Alternative Food Networks (AFN) is a concept that has emerged in opposition to conventional food systems and the global food regime. AFN are localized food networks that connect actors from food producers to consumers creating a pathway that strengthens ecological, social, and economic sustainability. Much of the literature on AFN focuses on geographies and food systems in the Global North, often recommending schemes such as farmers’ markets, community supported agriculture, organic certification, and fair trade. However, these strategies are not always appropriate for food systems in the Global South. In Colombia, small producers have maintained a parallel traditional food system, despite the growing pressure and investments to transition to a conventional food system. This research analyses the local food system of Cauca addressing the following questions: 1) what are the dynamics of the local food system in the Andean region of Cauca and 2) how can the local food system in the Andean region of Cauca be conceptualized as an alternative food network in the context of the Global South? To answer these questions, transdisciplinary research was carried out using SWOT analysis during multiple stakeholder workshops, followed by a reflexive thematic analysis of the results. The results show coexistence of both traditional and conventional food system dynamics, with participants assigning greater value to traditional food systems and agroecological production (akin to AFN literature), yet the economic insecurity and socio-political unrest that underlies daily life prohibits a more robust transition from conventional food system. It is argued that the understanding of AFN should be expanded to incorporate socio-cultural context as well as the dynamics of AFN in the Global South.